Diversidade de espécies de Anaplasma spp. em bovinos em Maputo, Moçambique - Fernandes, Simone de Jesus [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Embora espécies de Anaplasma spp. sejam agentes Rickettsiales altamente difundidos em ruminantes domésticos e selvagens, com ampla distribuição mundial, poucos estudos foram realizados até momento com o intuito de detectar e/ou investigar a diversidade de Anaplasma spp. circulantes em bovinos em Moçambique. No presente estudo, ensaios sorológicos e moleculares foram utilizados para investigar a ocorrência de Anaplasma spp. em 219 bovinos amostrados nos distritos de Boane, Magude, Matutuíne, Moamba e Namaacha em Maputo, Moçambique. No teste iELISA para detecção de anticorpos IgG anti- A. marginale, 86,3% (189/219) das amostras mostraram-se soropositivas. Em ensaios de qPCR para os genes msp1β de A. marginale e msp2 para A. phagocytophilum, 97,3% (213/219) e 2,74% (6/219) dos animais mostraram-se positivos, respectivamente. A combinação de dois protocolos diferentes de cPCR baseados no gene 16S rRNA evidenciou 100% de amostras positivas para Anaplasma spp. Sequências de 16S rRNA filogeneticamente relacionadas a A. platys, A phagocytophilum, ‘Candidatus Anaplasma boleense’, A. centrale, A. marginale e A. ovis foram detectadas neste estudo. Inferências filogenéticas baseadas nos genes msp4 e msp5 posicionaram as sequências obtidas no clado de A. marginale, com a evidência de circulação de 1 e 2 haplótipos diferentes para cada gene, respectivamente. Anaplasma sp. filogeneticamente associado a A. platys foi evidenciado nas análises filogenéticas baseadas nos genes 16S rRNA e groEL. Conclui-se que uma alta diversidade de espécies de Anaplasma sp. circulam em bovinos em Moçambique.

Although species of Anaplasma spp. are widespread Rickettsiales agents in domestic and wild ruminants, showing a worldwide distribution, few studies have been conducted in order to detect and/or investigate the diversity of Anaplasma spp. circulating in cattle in Mozambique. In the present study, serological and molecular tests were used to investigate the occurrence of Anaplasma spp. in 219 bovine sampled in the districts of Boane, Magude, Matutuíne, Moamba and Namaacha in Maputo, Mozambique. In the iELISA test for detection of IgG antibodies to A. marginale, 86.3% (189/219) of the samples were positive. In quantitative Real-time PCR tests targeting the msp1β genes of A. marginale and msp2 for A. phagocytophilum, 97.3% (213/219) and 2.74% (6/219) of the animals were positive, respectively. The combination of two different protocols of conventional PCR targeting the 16S rRNA gene evidenced 100% of positive samples for Anaplasma spp. Sequences of 16S rRNA phylogenetically related to A. platys, A. phagocytophilum, ‘Candidatus Anaplasma boleense', A. centrale, A. marginale and A. ovis were detected in this study. Phylogenetic analysis based on msp4 and msp5 genes positioned the obtained sequences in the clade of A. marginale, with the evidence of circulation of 1 and 2 different haplotypes for each gene, respectively. Anaplasma sp. phylogenetically related to A. platys was evidenced in the phylogenetic analyses based on the 16S rRNA and groEL genes. In conclusion,a high diversity ofAnaplasma species circulating in cattle in Mozambique.
Diversity of species of Anaplasma spp. in bovine in Maputo, Mozambique
Keywords: Anaplasma marginale; Anaplasma phagocytophilum; Anaplasma platys; Anaplasma centrale; Anaplasma ovis; Candidatus Anaplasma boleense